The Representation of Prevention-of-Mother-to-Child Transmission Service System in Surakarta Indonesia (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
The data trend showing the increase in number of HIV/AIDS case through perinatal transmission in Indonesia, including Surakarta, is worrying. This qualitative study with exploratory method took place in Surakarta on February to May, 2015. The units of analysis in this study were recipient and provider of Prevention of Mother-To-Child Transmission (PMTCT) service. The informants were selected using purposive sampling. The data was collected using observation, in-depth interview, Focus Group Discussion and documentation, and was then analyzed using Parsons’ system theory. PMTCT service system in Surakarta was ineffective because of HIV-positive women’s limited knowledge and information on PMTCT, unequal relation between provider and recipient of PMTCT service, medical decision making pattern that is inherent to service provider, and inadequate financial resource and supervision process. For that reason, an action plan is required to accommodate the need of women and children in term of budget allocation, program implementation and civil society involvement in PMTCT to prevent and to cope with HIV/AIDS.